Detangling the Crosstalk Between Ascaris, Trichuris and Gut Microbiota: What´s Next? - Castañeda, Sergio; Paniz-Mondolfi, Alberto; Ramírez, Juan David (Frontiers in Cellular and Infection Microbiology, 2022)
Helminth infections remain a global public health issue, particularly in low- and middle-income countries, where roundworms from theTrichuris and Ascaris genera are most prevalent. These geohelminths not only impact human health but most importantly also affect animal well-being, in particular the swine industry. Host-helminth parasite interactions are complex and at the same time essential to understand the biology, dynamics and pathophysiology of these infections. Within these interactions, the immunomodulatory capacity of these helminths in the host has been extensively studied. Moreover, in recent years a growing interest on how helminths interact with the intestinal microbiota of the host has sparked, highlighting how this relationship plays an essential role in the establishment of initial infection, survival and persistence of the parasite, as well as in the development of chronic infections. Identifying the changes generated by these helminths on the composition and structure of the host intestinal microbiota constitutes a field of great scientific interest, since this can provide essential and actionable information for designing effective control and therapeutic strategies. Helminths like Trichuris and Ascaris are a focus of special importance due to their high prevalence, higher reinfection rates, resistance to anthelmintic therapy and unavailability of vaccines. Therefore, characterizing interactions between these helminths and the host intestinal microbiota represents an important approach to better understand the nature of this dynamic interface and explore novel therapeutic alternatives based on management of host microbiota. Given the extraordinary impact this may have from a biological, clinical, and epidemiological public health standpoint, this review aims to provide a comprehensive overview of current knowledge and future perspectives examining the parasite-microbiota interplay and its impact on host immunity.